Between Monarchy and Demands for Political Change: Regionalisation and internationalisation of trade union activism in Swaziland - Gabriel Tati (Cadernos de Estudos Africanos, 2020)
This article examines how the trade unions in Swaziland have shifted their activism from local to regional and international arenas, crystallising their positions around new demands that attracted the ban of their activities. The reasons for such a shift are critically discussed in the light of contemporary political and economic crises affecting the kingdom of Swaziland. Using the social movement theory and interviews collected from union leaders, the article focuses particularly on the cross-border alliances which are built between, on the one hand, the federations of trade unions in Swaziland and the Congress of South African Trade Unions (COSATU) around political changes and on the other hand between the Swazi unions and international union confederations.